Theoretical Study on Heat Transfer in the Presence of Fouling - Abdulwahid Abdulnabi Al-Hallaf, Waqar (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
The fouling depositions of crude oil stream were studied theoretically in a shell and tube heat exchanger to investigate the effect of depositions on the heat transfer process. The employed heat exchanger was with steam flowing in the inner tubes and crude oil in the shell at different velocities and bulk temperatures. It is assumed that fouling occurs only on the heated stream side (crude oil). The analysis was carried out for turbulent flow heat transfer conditions with wide range of Reynolds number, bulk temperature and time. Many previously proposed models for fouling resistance were employed to estimate a new model for fouling rate. It is found that the fouling rate and consequently the heat transfer coefficient were affected by Reynolds number, Prandtls number, film temperature, activation energy, and time. The results obtained showed that fouling resistance decreased with the increasing of Reynolds number and Prandtls number, and increased with the increasing of film temperature and time. The analyses of results were compared with some experimental work and a reasonable agreement is attained.